O dispositivo de menoridade e as formas de governo das condutas na contemporaneidade - Martins, Maria Marta (2020)
Based on the thinking of Michel Foucault and in view of the concept of device as a neoliberal machinery, this doctoral research has as its object the ways of infantilization which are typical of the minority device that currently covers the Brazilian population. The corpus selected for analysis is composed of a set of statements from digital information media, predominantly from the journalistic discourse, which converges to a moralizing political discourse as a vector of the mechanisms and effects of minority and proceeds from three events of great visibility in the present: the High School Reform, in April 2016 and, following the backing of the Temer government's package of measures, the Social Security Reform proposal sent to Congress in 2016 and the amendments to the 2017 Labor Law; the closing of the Queermuseu art exhibition - Cartographies of Difference in Brazilian Art, in September 2017; and the murder of the city councelor Marielle Franco, in March 2018. Named archeogenealogical, the methodological path has in mind that, in terms of Foucault's Discourse Analysis, the method is a construction that includes both discursive and power / knowledge relationships and coincide with the lines covered by the mechanisms that operate the power devices and, therefore, the minority device. Thus, the method also includes the device. The thesis we intend to validate is that the minority device, whose operation is guided by certain infantilization techniques, is in place, in full operation and covering the whole Brazilian society of control, at the present It should be clarified that these infantile techniques which are unique to the minority device are not to be confused with Marxist alienation, or with other indoctrination processes in which the figures of the repressor and the repressed are present. Such technology of power is located in the scope of affection and protection through a phenomenon in which, spontaneously, many allow themselves to be led by some others. In the established path, what is perceived is that infantilization with all the nuances that the term carries (immaturity, insecurity, fear, submission ...) serves as a government technique that guides the conduct in the path of the interests of neoliberal capitalism. Coined in the universe of lights, the term minority refers to the individual's denial of access to clarification, understood as an exercise of thought through which self-conduct is operated. And that is how the vast majority of the population outsources the conduct of their own conduct, remaining in a state of minority. However, in the same space where the political and moral minority that we are dealing with operates, there is also the altering experience and different forms of resistance, through which the individual can change, make his own choices and assume the conduct of his own conduct.